(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
The current work utilizes the peel and pulp of the Iraqi eggplant to remove Alizarin Red S dye (ARS) from an aqueous solution. The isotherms of adsorption were studied and the factors that the effect them: temperature, the effect of surface nature and effect of ionic strength. The isotherms of adsorption of ARS on the peel were found obey the Freundlich, equation, but the isotherms of adsorption on the pulp were found to obey the Langmuir equation. At different temperatures, the adsorption process was studied, and it was found that when the temperature decreased, the adsorption increased. Based on the data we obtained in practice, the thermodynamic functions (∆H, ∆G, ∆S) were calculated as the process was exothermic, spontaneous, and more regular. The results showed that the effect of ionic strength (the presence of sodium chloride salt) was positive on the adsorption process for both surfaces. It was found that the nature of the surface has an effect on the adsorption process, as it was found that adsorption on the surface of the peels is more effective than on the surface of the pulp.